Referencing the sulcus line of the trochlear groove and removing intraoperative parallax errors improve femoral component rotation in total knee arthroplasty - Talbot, Simon (Knee Surg Sports Traumatol Arthrosc, 2015)
PURPOSE: Firstly, to assess and compare the accuracy and reproducibility of the sulcus line compared to Whiteside’s line. Secondly, to assess the accuracy of intraoperative techniques for using the rotational alignment of the trochlear groove to set femoral rotation. Thirdly, to assess the reproducibility of a trochlear alignment guide which removes parallax errors that occur when projecting the sulcus line onto the surface of the femur. Finally, to measure the result of combining the geometrically accurate sulcus line and the posterior condylar axis. METHODS: Three surgeons measured eight rotational angles on ten cadaveric femora. This included Whiteside’s line, the sulcus line and the techniques in which they can be referenced during surgery. RESULTS: Relative to the anatomical epicondylar axis, the sulcus line (mean −2.8°, SD 2.0°, range −5.4° to 0.8°) had significantly lower variance (F = 5.16, p = 0.036) than Whiteside’s line (mean −2.0°, SD 3.7°, range −6.0° to 3.4°). The trochlear alignment guide produced the best results of the intraoperative techniques by maintaining the accuracy of the sulcus line and projecting it onto the distal cut surface of the femur without change in rotational angle. CONCLUSION: The sulcus line is more accurate and reproducible than Whiteside’s line. Removing parallax errors during surgery improves femoral component rotation. The trochlear alignment guide produced accurate results suggesting that it may be beneficial in a clinical setting. Averaging the sulcus line and posterior condylar axis on the cut surface of the femur improved accuracy over the individual landmarks. Femoral component malrotation is a common cause of patient dissatisfaction and revision surgery. By isolating the rotational alignment of the trochlear groove using the sulcus line, and maintaining its accuracy with an intraoperative guide, we can decrease the risk of femoral component malrotation and improve patient outcomes.